Development of Silica-based Materials from Natural Sources as A Green Catalyst for Biofuel Production - Nugraha, Reva Edra; Aziz, Abdul; Sunarti, A.R Yelvia; Nurherdiana, Silvana Dwi; Mumtazah, Zuhriah; Sholeha, Novia Amalia; Nurmawati, Ardika; Islamiyah, Syuaibatul; Nandini, Atika; Saputro, Erwan Adi (Aceh International Journal of Science and Technology, 2024)
Mesoporous silica is a versatile material characterized by its highly ordered nanoporous structure with pore diameters ranging from 2 to 50 nanometers. This unique structure provides a large surface area and volume, making mesoporous silica an excellent candidate for various applications in adsorption, drug delivery, catalysis, and environmental remediation. Mesoporous silica can be synthesized using commercial or natural silica precursors such as mineral clay and other natural sources. Promising alternative sources of silica for synthesizing mesoporous materials encompass a range of materials, including various clay minerals such as kaolin, rectorite, halloysite, montmorillonite, sepiolite, hectorite, bentonite, talc, muscovite, paragonite, palygorskite, and chlorite. Other natural sources like beach sand, geothermal sludge, and sepiolite also show significant potential for mesoporous material synthesis. However, these sources have not been extensively explored and warrant further investigation in the field. The mesoporous silica from natural sources has been widely used as a catalyst for biofuel production via hydrocracking, catalytic cracking, and deoxygenation reactions